Conceptualising Human-centric Cyber Security in the Arctic in Light of Digitalisation and Climate Change - Klein, Joëlle; Hossain, Kamrul (Arctic Review on Law and Politics, 2020)
The following article revisits existing scholarship on human-centric approaches to security in cyberspace and argues that a holistic understanding of cyber security in the Arctic must include discussion of the use of cyber technology in the everyday lives of individuals and communities, addressing both the ways such tools enable and undermine human security. Simultaneously, the article contextualises the Arctic as a region undergoing rapid change as a result of climate change and increased digitalisation and seeks to understand the consequent implications for human security. In light of these considerations, the article analyses the existing constraints and possibilities that cyber security and digitalisation pose for human security and revisits them from a humancentric perspective of cyber security. It also seeks to contextualise such security influences in relation to the role of climate change and its influence on the region. Finally, several examples are discussed to underline the interdependent implications of digitalisation and climate change from a human-centric perspective of cyber security in the Arctic.